2022
DOI: 10.1177/21582440221109586
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Motives for Pursuing Postgraduate Studies and Causes of Late Completion: Supervisors and Supervisees’ Experiences

Abstract: This article is a product of a study that deployed a qualitative research approach to examine what motivates students in Tanzania to undertake postgraduate studies, and the causes of late completion of such studies. A total of 47 participants were involved in this study through focused group discussions and semi-structured interviews. The results revealed five distinct reasons why postgraduate students enter a doctoral or master’s degree course: employment prospects, better salary, career progression or change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
1
4
0
1
Order By: Relevance
“…Studies have shown that for many employed individuals, the prospects of improvement in career or the ability to perform better is a major motivating factor for enrolling in postgraduate program. 10 , 23 , 24 Similar findings were observed in this study where the majority of applicants were employed at a junior position and had decided independently to apply for the program, indicating some degree of self or intrinsic motivation.…”
Section: Discussionsupporting
confidence: 84%
“…Studies have shown that for many employed individuals, the prospects of improvement in career or the ability to perform better is a major motivating factor for enrolling in postgraduate program. 10 , 23 , 24 Similar findings were observed in this study where the majority of applicants were employed at a junior position and had decided independently to apply for the program, indicating some degree of self or intrinsic motivation.…”
Section: Discussionsupporting
confidence: 84%
“…For every one-unit increase in students' self-efficacy, students are more than 8 times more likely to plan to enroll in a master's program relative to not attending graduate school (Borrego et al, 2018). Amani et al (2022) used qualitative research methods to study the motivation of Tanzanian students for postgraduate study and found that the main reasons were to obtain promotions and better salaries, to make progress or changes in their careers, to develop themselves, to gain prestige or to achieve self-realization. Similar findings have been confirmed in other studies (De Los Santos et al, 2019;Jung, 2019;Makrygianni et al, 2023;Rock et al, 2023).…”
Section: Influencing Factors For Pursuing An MDmentioning
confidence: 99%
“…30 Pursuing a postgraduate degree is a challenging feat in itself and if not supported, students could drop out midway due to an incomplete thesis, insufficient achievement motivation, lacking learning strategies available, and low confidence. 31 Career opportunities appear to be a primary source of interest and motivation to pursue graduate degrees. For this study, these were expressed as practice specialization and opportunity for promotion.…”
Section: Demographic Profilementioning
confidence: 99%